Industrial Energy Efficiency study aid - Klimova, G. N. specialist in the field of power engineering Associate Professor of Tomsk Polytechnic University, Candidate of technical sciences 1976- (Tomsk Polytechnic University Publishing House, 2015)
This book considers issues, reviewed by the courses "Industrial Energy Efficiency and Energy Audit", "Optimization and Energy Saving Practices", "Energy and Resource Saving Practices for Industrial and Utility Facilities." The structure of power saving regulatory and legal framework is described herein, as well as organization and implementation of energy inspections for consumers, main energy efficiency increase in electrical energy supply systems of industrial enterprises, revenue metering of electrical energy in different voltage systems, calculation and performance analysis for industrial enterprise energy efficiency assessment.Developed for students trained in the field 13.04.02 "Electrical and Power Engineering".